Contemporary Applications of Teaching Pedagogy for Tamil Kindergarten using Sustainable Practices - Ramasamy, R Kanesaraj; Williams, Maria Josephine; Subramanian, Parameswaran; Batumalai, Vathana (2018)
Emerging technology becomes a part of life, and it also may reshape education system.The evolving of technologies in education and performance is yet to be implemented in the Tamil language. As of today, there is no contemporary application on the Tamil language which can encourage student centered learning to compare as recommended by 11th Malaysian Plan.Currently, the method using at alma mater is teaching and learning using econtent, but however, kindergarten teachers are not trained to utilize these available resources. In this proposal, we would like to propose creative and interactive teaching and learning mechanism for Tamil Government kindergarten. This will be able to instil the passion for learning the Tamil language. We will be implementing three main methods to study and propose a new teaching methodology for the school without changing the curriculum.As the output of this project, we will propose a new teaching methodology using the econtent specifically for the kindergarten students.The interactive application will be developed which will be suitable for the students as well this proposed project will allow Ministry of Education to control the curriculum content. Finally, we will evaluate the quality of students based on the rubrics given by the ministry to evaluate the quality and the improvement of the students.